WTO’S Trade Policy Review Mechanism (TPRM) and Indonesia’s Compliance in Agriculture Sector - Dewangga Dura Dematar (Institute of International Studies, 2019)
This article is designed to appraise TPRM as a monitoring instrument in WTO and understand how it affects Indonesia’s compliance in the agriculture sector. On paper, TPRM should be exercised as a surveillance system to boost transparency and compliance. However, the author doubts the current periodic, differentiated by economic power, and the self-serving reporting system of the TPRM. As this process is complicated and flexible, where often used as a diplomatic visit or excuses to initiate diplomatic relations between turbulent nations, the writer believes that TPRM is only the tip of the iceberg with unlimited complex problems underneath. Adapting instruments from International Law and Rational Choice Theory, the writer borrowed Guzman’s framework to determine how TPRM could affect Indonesia’s compliance in the agriculture sector. This article will give a better understanding of the monitoring process of an international institution, especially the one with no law enforcement system and held fundamentally by mutual respect and good faith.